Prakash versus figure of eight technique in sternal closure in CABG patients - Elsaify, Mohammad M.; Soltan, Hatem M.; Soliman, Rafik F.; Hagag, Mohamed Gamal (International Surgery Journal, 2019)
Background: Median sternotomy was recommended in 1957 by Julian for complete exposure of the heart. Despite the high importance of correct sternotomy, proper sternal closure is vital to ensure fewer post-operative complications. The sternum can be closed by wires and other methods. Sternal closure using the most suitable technique can dramatically reduce the risk of development of such complications. Methods: It is a prospective randomized comparative study of two patient groups, each included 30 patients, diagnosed of ischemic heart disease and underwent CABG. Group A with the patients’ sterna closed by figure of eight method and group B with multi-twist (Prakash) technique. Both groups were compared regarding postoperative pain and complications as superficial and deep sternal wound infections (SSWI, DSWI), wire removal and rewiring within six months of follow up. Results: The mean of minimum post sternotomy pain in group A patients was 24.50±11.7, whereas in patients of group B, it was 27±10.1. Only two patients (group A) suffered sternal dehiscence within six months follow up. The incidence of SSWI and DSWI among both groups was almost similar with only two patient of group A needed wire removal and one of them required rewiring. Conclusions: The multi-twist sternal closure provides better sternal stability after CABG especially in patients who are vulnerable to sternal dehiscence.